Investigating students’ reflection toward self-assessment on creative writing achievement in ESP course - Sumarni; Muhammad Miftah Fauzan; Samah Ali Mohsen Mofreh; Andi Anto Patak (Center for Humanities and Innovation Studies, 2018)
It not only seeks any ways of assessing student progress towards meeting outcome goals about professionalism, provides feedback and encourage students to take responsibility for setting and achieving high standards of performance, but also involve a direction to the whole teaching how great it supposed to be. This study investigates 45 students of 5 meetings English course at Computer and Informational Technology Faculty, Mulawarman University by using self-assessment followed by an in-depth interview. The instruments used for the survey is a self-made questionnaire based on literature review. In the beginning, a questionnaire was delivered to students to get primary students’ reflection of various writing tasks-specifically or general English terms in many genres - before seeking information was widely involved in an interview of 5 students. The results of this study revealed that 96% of students agreed that they had engaged in useful reflection using self-assessment to the course and 91% agreed that the experience was worthwhile. A further 76% of students agreed that they could see opportunities if many approaches appear in some ways as results of a various writing exercise. For specifically or General English terms of various writing tasks, mostly they favor a creative essay more than a specific essay. This study is believed that it might be as strong recommendation to attend the satisfactory grounding and integrating English on ESP. It also can support for future research what ESP designing supposed to be.